Plasma Homocysteine and Carotid Intima-Media Thickness in Type 1 Diabetes: A Prospective Study - Basu, Arpita (2014)
OBJECTIVE: Plasma homocysteine (tHcy) has been positively associated with carotid intima-media thickness (IMT) in non-diabetic populations and in a few cross-sectional studies of diabetic patients. We investigated cross-sectional and prospective associations of a single measure of tHcy with common and internal carotid IMT over a 6-year period in type 1 diabetes. RESEARCH DESIGN AND METHODS: tHcy levels were measured once, in plasma obtained in 1997-1999 from patients (n=599) in the Epidemiology of Diabetes Interventions and Complications (EDIC) study, the observational follow-up of the Diabetes Control and Complications Trial (DCCT). Common and internal carotid IMT were determined twice, in EDIC “Year 6” (1998-2000) and “Year 12” (2004-2006), using B-mode ultra-sonography. RESULTS: After adjustment, plasma tHcy [median (interquartile range): 6.2 (5.1, 7.5) μmol/L] was significantly correlated with age, diastolic blood pressure, renal dysfunction, and smoking (all p<0.05). In an unadjusted model only, increasing quartiles of tHcy correlated with common and internal carotid IMT, again at both EDIC time-points (p<0.01). However, multivariate logistic regression revealed no significant associations between increasing quartiles of tHcy and the 6-year change in common and internal carotid IMT (highest vs. lowest quintile) when adjusted for conventional risk factors. CONCLUSIONS: In a type 1 diabetes cohort from the EDIC study, plasma tHcy measured in samples drawn in 1997-1999 was associated with measures of common and internal carotid IMT measured both one and seven years later, but not with IMT progression between the two time-points. The data do not support routine measurement of tHcy in people with Type 1 diabetes.